Changing Americans' Attitudes about Immigration: Using Moral Framing to Bolster Factual Arguments. Issue 1 (March 2022) - Voelkel, Jan G.; Malik, Mashail; Redekopp, Chrystal; Willer, Robb
Our tendency to interpret facts in ways that are consistent with our prior beliefs impedes evidence-based attempts to persuade partisans to change their views on pressing societal issues such as immigration. Accordingly, most prior work finds that favorable information about the impact of immigration has little or no influence on policy preferences. Here, we propose that appealing to individuals' moral values can bolster the persuasive power of informational interventions. Across three experiments (total N = 4, 616), we find that an argument based on the value of in-group loyalty, which emphasized that immigrants are critical to America's economic strength, combined with information about the economic impact of legal immigration, significantly increased Americans' support for legal immigration. We also find a significant effect of the moral component of this message alone, even without factual information. These results show that moral arguments can strengthen the persuasiveness of informational appeals.